2017
DOI: 10.2967/jnumed.116.184713
|View full text |Cite
|
Sign up to set email alerts
|

Resin Versus Glass Microspheres for 90Y Transarterial Radioembolization: Comparing Survival in Unresectable Hepatocellular Carcinoma Using Pretreatment Partition Model Dosimetry

Abstract: The aim of this study was to compare survival of patients treated for unresectable hepatocellular carcinoma (uHCC) with 90 Y transarterial radioembolization (TARE) using pretreatment partition model dosimetry (PMD). Methods: We performed a retrospective analysis of prospectively collected data on 77 patients consecutively treated (mean age 6 SD, 66.4 6 12.2 y) for uHCC (36 uninodular, 5 multinodular, 36 diffuse) with 90 Y TARE (41 resin, 36 glass) using pretreatment PMD. Study endpoints were progression-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 21 publications
0
31
1
Order By: Relevance
“…Despite the need for larger injection volumes and subsequent higher microembolic effects for resin-based spheres due to lower relative activity, no difference has been noted thus far in clinical response [41]. Of note, RE by microspheres does not result in macrovascular embolization; thus, the hypertrophy of the liver is probably induced by radiation effects [14,21,42].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the need for larger injection volumes and subsequent higher microembolic effects for resin-based spheres due to lower relative activity, no difference has been noted thus far in clinical response [41]. Of note, RE by microspheres does not result in macrovascular embolization; thus, the hypertrophy of the liver is probably induced by radiation effects [14,21,42].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggested that the prescribed radiation activity might be significantly lower for resin than for glass microspheres, which may in part result from their different specific activities [31, 32]. However, this difference in activity does not appear to lead to a significant survival difference between the two types of treatment [33]. Postprocedural planar, SPECT, or SPECT/CT imaging with the broad-spectrum bremsstrahlung radiation is done to confirm proper localization of the therapeutic activity in the intended hepatic region.…”
Section: Selective Internal Radioembolization Of Malignant Liver Lesionsmentioning
confidence: 99%
“…The 90 Y-TARE planning and procedure was made as previously described [ 34 ]. Briefly, before 90 Y-TARE, all patients underwent a pretherapy SPECT/CT with intra-arterial administration of 120–180 MBq of 99m Tc-MAA.…”
Section: Methodsmentioning
confidence: 99%
“…In many of these factors, imaging is essential and therefore plays an important role in the management. Multiple studies have shown a correlation between standardized uptake value (SUV) of HCC on 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) and outcomes following different systemic and locoregional treatments [ 6 16 ], including more recently transarterial radioembolization with Yttrium-90 ( 90 Y-TARE) [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%